Genome-wide analysis of repeat diversity across the family Musaceae - Novák, Petr; Hřibová, Eva; Neumann, Pavel; Koblížková, Andrea; Doležel, Jaroslav; Macas, Jiří (PloS one, 2014)
BACKGROUND: The banana family (Musaceae) includes genetically a diverse group of species and their diploid and polyploid hybrids that are widely cultivated in the tropics. In spite of their socio-economic importance, the knowledge of Musaceae genomes is basically limited to draft genome assemblies of two species, Musa acuminata and M. balbisiana. Here we aimed to complement this information by analyzing repetitive genome fractions of six species selected to represent various phylogenetic groups within the family. RESULTS: Low-pass sequencing of M. acuminata, M. ornata, M. textilis, M. beccarii, M. balbisiana, and Ensete gilletii genomes was performed using a 454/Roche platform. Sequence reads were subjected to analysis of their overall intra- and inter-specific similarities and, all major repeat families were quantified using graph-based clustering. Maximus/SIRE and Angela lineages of Ty1/copia long terminal repeat (LTR) retrotransposons and the chromovirus lineage of Ty3/gypsy elements were found to make up most of highly repetitive DNA in all species (14-34.5% of the genome). However, there were quantitative differences and sequence variations detected for classified repeat families as well as for the bulk of total repetitive DNA. These differences were most pronounced between species from different taxonomic sections of the Musaceae family, whereas pairs of closely related species (M. acuminata/M. ornata and M. beccarii/M. textilis) shared similar populations of repetitive elements. CONCLUSIONS: This study provided the first insight into the composition and sequence variation of repetitive parts of Musaceae genomes. It allowed identification of repetitive sequences specific for a single species or a group of species that can be utilized as molecular markers in breeding programs and generated computational resources that will be instrumental in repeat masking and annotation in future genome assembly projects.
Keywords: Sequence Analysis, DNA; Phylogeny; DNA rostlinná; repetitivní sekvence nukleových kyselin; sekvenční analýza DNA; Repetitive Sequences, Nucleic Acid; DNA, Plant; Musaceae; banánovníkovité; Genetic Variation; molekulární evoluce; Evolution, Molecular; Genome, Plant; genom rostlinný; genetická variace; Computational Biology; fylogeneze; výpočetní biologie